Improvements in Psychological and Occupational Well-being Following a Brief Yoga-Based Program for Education Professionals - Natalie L Trent PhD; Sara Borden MBA; Mindy Miraglia MSc; Edi Pasalis MBA; Jeffery A Dusek PhD; Sat Bir S Khalsa PhD (SAGE Publishing, 2019)
Objective The purpose of this study was to examine changes in psychological and occupational well-being in education professionals who attended a yoga-based program. Methods Education professionals who attended a 3-day yoga-based RISE (resilience, integration, self-awareness, engagement) program were recruited to participate. RISE was administered at the Kripalu Center for Yoga & Health. Measures of psychological and occupational well-being, and health-related behaviors were completed before (baseline), after (post), and 2 months after RISE (follow-up). Forty-four participants completed baseline and post and were included in the analysis. Of those, 33 participants also completed the follow-up. Paired samples t tests were used to compare scores between time points. Results Compared to baseline, at post, participants showed improvements in perceived stress, mindfulness, empowerment, positive affect, negative affect, self-compassion, total work engagement, vigor, sleep quality (all P values < .001), resilience, satisfaction with life, as well as exhaustion and professional efficacy which are dimensions of burnout (all P values < .01). At the follow-up, significant improvements were maintained for mindfulness, empowerment, self-compassion, sleep quality (all P values < .001), resilience, vigor, and exhaustion (all P values < .01) and positive affect, satisfaction with life, and work engagement (all P values < .05). Conclusions These findings suggest that the yoga-based RISE program improves psychological and occupational well-being in education professionals. In addition, participants reported that attending RISE was feasible, they could continue using RISE practices long-term, shared them with work colleagues, and reported that RISE positively impacted both their daily lives and workplace environment. With these promising results, additional controlled research is warranted.